Favourable effect of ?-glucan treatment against cisplatin-induced reproductive system damage in male rats - Kaya, Kursat; Ciftci, Osman; Aydin, Muhterem; Cetin, Asli; Basak, Nese (Wiley, 2019)
The aim of this study was to investigate the potential beneficial effects of beta-glucan treatment against oxidative, histological and spermatological damage caused by cisplatin on the male reproductive system. Twenty-eight Sprague Dawley male rats were used in the study. The rats were randomly divided into four equal-sized groups: a control group, cisplatin group (7 mg/kg in a single-dose cisplatin administered intraperitoneally), beta-glucan group (beta-glucan given at a dose of 50 mg kg(-1) d(-1) for 14 day) and a cisplatin plus beta-glucan group (cisplatin and beta-glucan administered together at the same dose). Cisplatin administration induced an increase in the level of thiobarbituric acid-reactive substances, a lipid peroxidation indicator. It induced a decrease in enzymatic (superoxide dismutase, catalase and glutathione peroxidase) activities and nonenzymatic (reduced glutathione) antioxidant levels. In addition, cisplatin caused both histological and spermatological damage, as shown by a decrease in sperm motility and epididymal sperm concentrations and an increase in abnormal sperm rates. The beta-glucan treatment improved cisplatin-induced oxidative, histological and spermatological damage. This study revealed that beta-glucan treatment provided prevention against male reproductive system damage caused by cisplatin. These preventative effects were likely due to its antioxidant properties.
Keywords: cisplatin; oxidative stress; spermiotoxicity; testicular damage; beta-glucan